Strategi Guru dalam Mengembangkan Motorik Kasar Anak Usia 5-6 Tahun di TK Baiturrahman Jempong Barat Kota Mataram: Teacher Strategies in Developing Gross Motor Skills in Chirdren Age 5-6 Years at Biturrahman Kindergarten, Jempong Barat, Mataram - Sri Wahyuni; Diana, Raden Rachmy (Universitas Ngudi Waluyo, 2025)
This research aims to determine the teacher’s strategies in developing gross motor skills of children aged 5-6 years, the teacher’s obstacles and solutions in developing children’s gross motor skills, as well as to determine the development of children’s gross motor skills at TK Baiturrahman Jempong Barat Mataram. This research uses a qualitative approach with a descriptive type. Data collection techniques used include observation, interviews, and documentation. While data analysis is carried out by data reduction, data presentation, and verification. Data validity checks are carried out by observation persistence and triangulation. Based on the research results, it shows that the teacher’s strategies in developing gross motor skills of children aged 5-6 years at TK Baiturrahman Jempong Barat Mataram have three kinds of strategies used, including: (1). Learning strategies through play. (2). Learning strategies through singing. (3). Group learning strategies. The obstacles faced by teachers in learning activities to develop children’s gross motor skills include: first, lack of teacher competence, second, child factors, and third, inadequate facilities. The development of children’s gross motor skills at TK Baiturrahman is said to be capable or developing well. Where children are able to imitate movements according to songs such as gymnastic movements and dance movements. In addition, children are able to walk on tiptoes. Children are able to walk forward and backward 10 steps, children are able to jump with 1 or 2 feet, children are able to combine squatting and jumping, and children are able to run fast without difficulty. This study highlights the importance of teacher creativity in selecting and modifying learning strategies to make physical activities enjoyable and suited to children’s needs. The research contributes to the development of early childhood education, particularly in the field of gross motor learning strategies based on play activities. Practically, the results of this study can serve as a reference for teachers and early childhood education institutions in designing more effective learning activities to stimulate children’s physical development while enhancing their health, self-confidence, and social skills. ABSTRAK Penelitian ini bertujuan untuk mengetahui strategi guru dalam mengembangkan motorik kasar anak usia 5-6 tahun, kendala guru dan solusi dalam mengembangkan motorik kasar anak, serta mengetahui perkembangan motorik kasar anak di TK Baiturrahman Jempong Barat Mataram. Penelitian ini menggunakan pendekatan kualitatif dengan jenis deskriptif. Teknik pengumpulan data yang digunakan melalui tiga cara yaitu observasi, wawancara dan dokumentasi. Analisis data dilakukan dengan reduksi data, penyajian data dan verification. Pengecekan keabsahan data dilakukan dengan ketekunan pengamatan dan triangulasi. Berdasarkan hasil penelitian menunjukkan bahwa strategi guru dalam mengembangkan motorik kasar anak usia 5-6 tahun di TK Baiturrahman Jempong Barat Mataram memiliki tiga macam strategi yang digunakan antara lain: (1). Strategi pembelajaran melalui bermain. (2). Strategi pembelajaran melalui bernyanyi/lagu dan menari. (3). Strategi pembelajaran kelompok. Adapun kendala yang dihadapi guru dalam kegiatan pembelajaran untuk mengembangkan motorik kasar anak antara lain: pertama, Kurangnya kompetensi guru, kedua faktor anak dan ketiga, fasilitas yang kurang memadai. Perkembangan motorik kasar anak di TK Baiturrahman sudah dikatakan mampu atau berkembang dengan baik. Dimana anak mampu menirukan gerakan sesuai lagu seperti gerakan senam dan gerakan saat menari. Selain Anak mampu berjalan dengan kaki dijinjit, Anak mampu berjalan maju dan mundur, anak mampu melompat dengan 1 atau 2 kaki, Anak mampu kombinasi jongkok lalu melompat dan anak mampu berlari cepat tanpa kesulitan. Penelitian ini menunjukkan pentingnya kreativitas guru dalam memilih dan memodifikasi strategi pembelajaran agar kegiatan fisik menjadi menyenangkan serta sesuai dengan kebutuhan anak. Penelitian ini memberikan kontribusi bagi pengembangan ilmu pendidikan anak usia dini, khususnya dalam bidang strategi pembelajaran motorik kasar berbasis aktivitas bermain. Secara praktis, hasil penelitian ini dapat dijadikan acuan bagi guru dan lembaga PAUD dalam merancang kegiatan pembelajaran yang lebih efektif untuk menstimulasi perkembangan fisik anak sekaligus meningkatkan kesehatan, kepercayaan diri, dan kemampuan sosial mereka.